Highly fluorescent nitrogen-doped carbon dots with excellent thermal and photo stability applied as invisible ink for loading important information and anti-counterfeiting. Issue 2 (1st December 2016) - Liu, Yingbo; Zhou, Liang; Li, Yanan; Deng, Ruiping; Zhang, Hongjie
Abstract : Highly photo/thermal stable nitrogen-doped carbon dots with a QY of 75% are promising for loading important information and anti-counterfeiting. Abstract : High quantum yields (QY) and stable performances are prerequisites for implementing carbon dots in practical applications. In this study, we demonstrate that nitrogen-doped carbon dots (N-CDs), which were prepared via the hydrothermal treatment of citric acid (CA) and tris(hydroxymethyl)methyl aminomethane (Tris), have a high QY of 75%, together with excellent thermal and photo stability. These N-CDs deliver an excellent thermal stability performance over the temperature range of 25 °C to 95 °C, and even at a heating temperature of 90 °C for 360 min. Upon exposure to UV illumination with a radiant intensity of 20 mW cm −2, 96% fluorescence intensity is retained. This florescence stability performance is probably due to the chemical composition and steric effect of the nitrogen-doping agent. Furthermore, the remarkable optical properties of these N-CDs allow them to be used as invisible ink for loading important information and advanced anti-counterfeiting.